Diffusion Tensor Imaging Revealed Microstructural Changes in Normal-Appearing White Matter Regions in Relapsing–Remitting Multiple Sclerosis - Bao, Jianfeng; Tu, Hui; Li, Yijia; Sun, Jubao; Hu, Zhigang; Zhang, Fengshou; Li, Jinghua (Frontiers in Neuroscience, 2022)
Axons and myelin sheaths are physical foundation for white matter (MW) to perform normal functions. Our previous study found the metabolite abnormalities in frontal, parietal and occipital normal appearing white matter (NAWM) regions in multiple sclerosis (MS) patients by applying 2D 1H magnetic resonance spectroscopic imaging (MRSI) method. Since the metabolite change may associate with the microstructure changes, we used diffusion tensor imaging (DTI) to assess the integrity of NAWM in this study. DTI scan was performed on 17 clinically definite relapsing-remitting multiple sclerosis (RRMS) patients and 21 age-matched healthy controls. DTI measures including fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) were extracted from seventeen predefined regions of interest (ROIs), which were generated by nonlinear registered WM atlas of Johns Hopkins University (JHU, ICBM-DTI-81) in the native space excluding a lesion probabilistic map. The mean values of FA, MD, AD and RD were compared between different groups in the same ROIs. A probabilistic lesion map was successfully generated and the lesions were then eliminated from WM templates. We found that the RRMS patients had statistically significant lower (all p<0.001) FA in the whole corpus callosum, both sides of anterior corona radiate, and right posterior thalamic radiation. What’s more, RRMS patients show significant higher MD in both sides of anterior corona radiate (p<0.001), superior corona radiate (p<0.001) and genu of the corpus callosum (p<0.01).While, all AD values increased, and both sides of external capsule (p<0.01), posterior thalamic radiation (p<0.001), right superior corona radiate (p<0.01), left anterior corona radiate (p<0.01) and left Tapetum (p<0.01) NAWM show statistical significance. All NAWM tracts showed increasing RD values in RRMS patients and both side superior corona radiates (p<0.001), anterior corona radiates (p<0.001), posterior thalamic radiation (p<0.001), right external capsule (p<0.01) and genu corpus callosum (p<0.01) reach statistical significance. With a ready-made WM atlas and lesion probabilistic map, our study revealed a widespread microstructure change in NAWM in RRMS patients, in support of the hypothesis that demyelination, accumulation of inflammatory cells and the axonal injury RRMS. The DTI-based metrics could be considered as potential noninvasive biomarkers of disease severity.